THE INTERCONNECTION BETWEEN PERSONALITY DIMENSIONS AND PARTICIPATORY BEHAVIOUR OF STUDENTS IN STUDENT ORGANIZATION - Markovikj, Marijana; Serafimovska, Eleonora (Institute for Sociological, Political and Juridical Research, 2017)
During May 2017 year the field research among students at University of “Ss. Cyril and Methodius” (UKIM) in Skopje was conducted. The main goal of this research was to explore the perception of student participation (as an indicator for citizenship participative behavior) in student organization at the University of “Ss. Cyril and Methodius” and the image of this organization among students. The total number of respondents was 669. Respondents were students from 1 till 4 year from almost all faculties which constitute UKIM. Questioner has been prepared for the purpose of this research and also Five Factorial personality test was used - short version of IPIP NEO, which is constructed according to McCrae and Costa’s personality theory. Regarding to this theory five basic dimensions, which are biologically given, interact with external influences including culture, in shaping the skills, habits, tastes, and values which construct the characteristic adaptation of the individual. Beside IPIP NEO, two dimensions of the Laponce questionnaire (concerning minority effect), one on the significance of the social role of the students, and the second on their treatment by the state were applied. The findings of this research pointed that dimensions: agreeableness (A) as the tendency to be compassionate and cooperative rather than suspicious and antagonistic toward others, and conscientiousness (C), the tendency to show self-discipline, act dutifully, are relevant dimensions which influenced students participative behavior in some aspects and affect citizenship participative behavior, but only if the social role of student is important.
Keywords: participative behavior, personality dimensions, agreeableness, conscientiousness, social roles